Nursing students' reflections on an interprofessional placement in ambulatory care. Issue 4 (3rd July 2016) - Saunders, Rosemary; Singer, Rachel; Dugmore, Helen; Seaman, Karla; Lake, Fiona
Abstract: Reflection has been identified as key to interprofessional education as it facilitates a focus on interprofessional communication, collaborative practice and professional roles, while contributing to debunking ingrained understandings of roles and behaviours. The aim of this study is to explore the written reflections of nursing students following an interprofessional placement in ambulatory care. A deductive analysis of nursing student reflective journal entries mapped against the university interprofessional framework was conducted. A purposeful sample of 19 graduate entry Master of Nursing Science students participating in a two-week interprofessional educational placement completed a reflective journal relating to an interprofessional placement in ambulatory care. The analysis of the journals found that all students were able to reflect on their interprofessional clinical experience, but the ability to reflect varied between students. Despite the challenges that some nursing students experienced in achieving deep levels of reflection, the study demonstrated the usefulness of incorporating reflective journals into nursing curriculums and as part of interprofessional practicums.